Expression of the axon guidance factor Slit2 and its receptor Robo1 in patients with Hirschsprung disease: An observational study. Issue 33 (20th August 2021) - Kong, Meng; Zhou, Tao; Xiang, Bo
Abstract : Abstract: Hirschsprung disease (HD) is a common form of digestive tract malformation in children. However, the pathogenesis of HD is not very clear. This study aimed to investigate the expression of slit guidance ligand 2 (Slit2) and roundabout 1 (Robo1) in patients with HD. From January 2018 to January 2019, 30 colon specimens from children with HD undergoing surgical resection at the Department of Surgery in Qilu Children's Hospital of Shandong University were obtained. These specimens were divided into the normal segment group, the transitional segment group and the spastic segment group. Immunohistochemical staining, Western blotting, and real-time polymerase chain reaction were used to measure the expression of Slit2 and Robo1 in the intestinal walls of normal, transitional, and spastic segments. Immunohistochemical staining and Western blot analyses showed high levels of the Slit2 and Robo1 proteins in normal ganglion cells in children with HD, lower levels in transitional ganglion cells, and no expression in spastic segments, with significant differences between groups ( P  < .05). Similarly, the real-time polymerase chain reaction results were consistent with the Western blot analysis results. The expression of Slit2 and Robo1 decreases significantly in the spastic segment of the intestinal tract in patients with HD.